The Impact of Hydraulic Retention Time on the Biomethane Production from Palm Oil Mill Effluent (POME) in Two-Stage Anaerobic Fluidized Bed Reactor - Ramadhani, Laily Isna; Damayanti, Sri Ismiyati; Sudibyo, Hanifrahmawan; Azis, Muhammad Mufti; Budhijanto, Wiratni (Center of Biomass & Renewable Energy, Diponegoro University, 2021)
Indonesia is currently the most significant crude palm oil (CPO) producer in the world. In the production ofCPO, 0.7m3 of Palm Oil Mill Effluent (POME) is emitted as the wastewater for every ton of fresh fruit bunches processed in the palm oil mill.With the increasing amount of CPO production, an effective POME treatment system is urgently required to prevent severe environmental damage. The high organic content in the POME is a potential substrate forbio-methane production. The biomethane production is carried out by two groups of microbes, i.e., acidogenic and methanogenic microbes. Each group of bacteria performs optimally at different optimum conditions. To optimize the biomethane production, POME was treated sequentially by separating the acidogenic and methanogenic microbes into two stages of anaerobic fluidized bed reactors (AFBR). The steps were optimized differently according to the favorable conditions of each group of bacteria. Although perfect separation cannot be achieved, this study showed that pH control could split the domination of the bacteria, i.e., the first stage (maintained at pH 4-5) was dominated by the acidogenic microbes and the second stage (kept neutral) was governed by methanogens. In addition to the pH control, natural zeolitewas added as microbial immobilization media in the AFBR to improve the performance of the microorganisms, especially in preventing microbial wash out at short hydraulic retention time (HRT). This study was focused on the understanding of the effect of HRT on the performance of steady-state continuous AFBR. The first stage as the acidogenic reactorwas rununder acidic conditions (pH 4-5) at five different HRTs. In comparison, the second stage as the methanogenic reactorwasrun under the neutral condition at four different HRTs. In this work,short HRT (5 days) resulted in better performance in both acidogenic AFBR and methanogenic AFBR. The immobilization media was hence essential to reduce the risk of washout at such a short HRT. The two-stage system also resulted in quite a high percentage of soluble chemical oxygen demand (sCOD) removal, which was as much as 96.06%sCOD.